Externalizing Anti-Blackness: Racialized Immobilization and Migrant Counter-Archives in Tunisia’s Borderlands of Abandonment - Córdova Morales, Edgar (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
This article examines the EU’s border externalization in Tunisia as a racialized project of governance rooted in longer genealogies of anti-Blackness and exclusion. Drawing on feminist, embodied ethnography, it traces how fast and slow violence—expulsions, bureaucratic immobilization, and everyday racism—govern and devalue Black migrant life. Yet through practices of care, documentation, and solidarity, migrants produce counter-archives that make this violence legible and contest its legitimacy. The article reveals externalization as a mechanism of racial domination and a terrain of political presence.